Explaining investor preference for cash dividends - Shefrin, Hersh M.; Statman, Meir (Journal of Financial Economics, 1984)
The well-known tendency of investors to favor cash dividends emerges quite naturally in two new theories of choice behavior [the theory of self-control due to Thaler and Shefrin (1981), and the version of prospect theory set out by Kahneman and Tversky (1979)]. Although our treatment is novel when viewed from the perspective of standard financial theory, it provides explanations for a phenomenon that has long been described as perplexing.